ANALISIS KEMAMPUAN MENULIS CERPEN MELALUI TEKNIK RUMPANG PADA KELAS IV SEKOLAH DASAR - Mega Krisdiana; Siti Malihah; Nana Suhana; Titin Suhartini; Yuyu Yuhana (SCHOOL EDUCATION JOURNAL PGSD FIP UNIMED, 2023)
The purpose of this study was to find out how to analyze the ability to write short stories through the gap technique in class IV of elementary school. This research was conducted in several elementary schools, namely: SDN Ciawi 2, SDN Sukadame 2, SDN Sentul 1 and SDN Baros 3 with a total population of 5 elementary schools for each student. The research used is included in the type of qualitative research. To explain the results of research using descriptive method. Data collection techniques used are observation and interviews. Based on the results and discussion previously described, it can be concluded that the analysis of the ability to write short stories through the gap technique in class IV elementary school students produces a score of 69.5% with the High criteria. This is evidenced by the learning outcomes of students in answering the gaps in the short story text on the LKPD given by their class teacher. The results of the analysis of the ability to write short stories of students from SDN Ciawi 2 were 72% included in the high criteria, 66% of SDN Sukadame 2 were included in the high criteria, SDN Sentul 1 was 68% included in the high criteria and SDN Baros 3 was 72% fall into the high criteria.